PENINGKATAN KESEJAHTERAAN EKONOMI MASYARAKAT DENGAN PELATIHAN SUMBERDAYA MANUSIA MELALUI PEMANFAATAN LIDI MENJADI HASIL KEWIRAUSAHAAN - Imam Mashuri; Fathi Hidayah (ABDI KAMI: Jurnal Pengabdian Kepada Masyarakat, 2019)
The welfare of rural communities can be improved by training their human resources to have the expertise to be able to process and utilize the materials provided by nature through a training program for making sticks. Stick making skills training processes stick waste into sticks that have artistic value and selling price. Which in turn can be a result of citizen entrepreneurship, and become a source of additional income for citizens